Efek Umur, Ukuran Perusahaan, Likuiditas, Serta Profitabilitas pada Manajemen Laba pada Perusahaan Pertambangan di BEI (2020-2023) - Tombe, Clara; Kumalasari, Fitri; Triani, Neks (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate various factors influencing earnings management practices in mining sector companies listed on the Indonesia Stock Exchange (BEI). The research population includes mining companies registered on the BEI during the 2020-2023 period. Using a purposive sampling method, 16 companies were selected as the study sample based on specific criteria over a four-year period. Data were sourced from company financial reports and analyzed using multiple linear regression with SPSS software. The research results indicate that, simultaneously, company age, company size, liquidity ratio, and profitability influence earnings management. Meanwhile, partially, each of these variables also has a significant impact on earnings management.